Conventional concept «age of sexual consent» in the Criminal Code of Ukraine: modern state and prospects - Дудоров, О. О.; Задоя , К. П. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2019)
Many factors influence the criminalization of acts in the sexual sphere, including the need for the state to fulfill its international legal obligations. In recent years, there has been a tendency in the European legal space towards unification of legislation in terms of determining the grounds for criminal liability for offenses in this area. A serious revision of section IV of the Special Part of the Criminal Code of Ukraine during 2017–2018 has been the result of the perception by the domestic legislator of the approaches, developed by the Council of Europe, namely the Istanbul and Lanzarote Conventions. The purpose of the study is to critically comprehend today’s implementation of the conventional concept «age of sexual consent» in Ukraine and to clarify the legal nature and prospects of this criterion for determining the limits of criminal behavior in the sexual sphere, in particular, in the context of the relationship between provisions of the mentioned conventions. It has been proved that the means of introducing the concept «age of sexual consent» inherent in the Criminal Code in force is characterized by a number of defects. In particular: 1) the established grading of the victim’s age, although allowing to differentiate criminal liability for committing acts of sexual nature against children, does not follow from Art. 18 of the Lanzarote Convention; 2) the optimality of fixing the 14-year age in parts 4 of Art. 152, art. 153 of the Criminal Code does not look indisputable. Lack of proper justification is inherent in the 16-year age criterion, which appears in Part 1 of Art. 155 of the Criminal Code; 3) use of the wording «natural or unnatural sexual intercourse» in Part 1 of Art. 155 of the Criminal Code not only violates the rule of unity of legislative terminology within Section IV of the Special Part of the Criminal Code but also does not correspond to the cross-conventional notion of «sexual activity with a child»; 4) contrary to the opinion of the developers of the relevant bill, there are no reasons to recognize the updated Art. 155 of the Criminal Code as execution of Art. 18 of the Lanzarote Convention as to the establishment of the age, prior to which engaging in sexual activity with a child is prohibited. Since the previous version of Part 1 of Art. 155 of the Criminal Code and the current version of this criminal law provision describe different types of behavior, there is no legal continuity between them; 5) although Art. 152 and Art. 153 of the Criminal Code, updated in accordance with the Istanbul Convention, embody the concept under consideration, they do not take into account the requirements of Part 3 of Art. 18 of the Lanzarote Convention on the impact of criminal liability for sexual activities, regarding the difference in the age of participants in such activities. It has been established that the main trend in the field of study, which has been reflected in the Istanbul Convention as a more modern document than the Lanzarote Convention, and which (the trend) more and more European countries join, consists of the introduction of criminal liability for any sexual behavior, carried out in the absence of the victim’s voluntary consent. This makes it possible to put forward the doctrinal approach for a professional discussion, which outlines the refusal of direct (textual) reflection in the Criminal Code of the concept «age of sexual consent». It is a fact that the role of a crime-forming feature in this case was also not played by the victim not reaching a certain age, defined by law, but by the absence of the victim’s voluntary consent, as is characteristic of sexual violence under the Istanbul Convention. It has been shown that this allowed, among other things, to consider legal assessment of sexual intercourse with a minor and other sexual penetration into the body of such victim, which is traditional for domestic court practice and is based on the use of the mental helplessness notion.

Анотація. На криміналізацію діянь у сексуальній сфері впливає чимало факторів, серед яких – необхідність виконання державою взятих на себе міжнародно-правових зобов’язань. Останніми роками в європейському правовому просторі простежується тенденція до уніфікації законодавства в частині визначення підстав кримінальної відповідальності за правопорушення у вказаній сфері. Серйозне оновлення протягом 2017–2018 рр. розділу IV Особливої частин Кримінального кодексу України стало результатом сприйняття вітчизняним законодавцем підходів, вироблених Радою Європи у межах Стамбульської та Лансаротської конвенцій. Метою дослідження є критичне осмислення сучасного стану реалізації в Україні конвенційного концепту «вік сексуальної згоди» та з’ясування перспектив цього критерію визначення меж злочинної поведінки у сексуальній сфері, зокрема, в контексті співвідношення положень згаданих конвенцій. Доведено, що притаманний чинному КК спосіб запровадження концепту «вік сексуальної згоди» характеризується низкою вад. Серед них: 1) встановлена градація віку потерпілого, хоча і дозволяє диференціювати кримінальну відповідальність за вчинення дій сексуального характеру щодо дітей, зі ст. 18 Лансаротської конвенції не випливає; 2) оптимальність закріплення 14-річного віку у частинах 4 ст. 152, ст. 153 КК не виглядає безспірною. Відсут- ність належного обґрунтування притаманна і 16-річному віковому критерію, який фігурує у ч. 1 ст. 155 КК; 3) використання в ч. 1 ст. 155 КК звороту «природні або неприродні статеві зносини» не лише порушує правило єдності законодавчої термінології в межах розділу IV Особливої частини КК, а й не відповідає наскрізному конвенційному поняттю «діяльність сексуального характеру з дитиною»; 4) оновлену ст. 155 КК усупереч думці розробників відповідного законопроекту немає підстав визнавати виконанням ст. 18 Лансаротської конвенції щодо встановлення «віку сексуальної згоди». Оскільки попередня редакція ч. 1 ст. 155 КК і чинна редакція цієї кримінально-правової норми описують різні типи поведінки, між ними відсутня правова наступність; 5) оновлені відповідно до Стамбульської конвенції ст. 152 і ст. 153 КК, хоча і втілюють аналізований концепт, не беруть до уваги вимогу ч. 3 ст. 18 Лансаротської конвенції щодо впливу на кримінальну відповідальність за сексуальну діяльність різниці у віці учасників такої діяльності. Встановлено, що основна тенденція у досліджуваній сфері, яка знайшла відображення в Стамбульській конвенції як більш сучасному порівняно з Лансаротською конвенцією документі, полягає в запровадженні кримінальної відповідальності за будь-яку сексуальну поведінку, здійснювану за відсутності добровільної згоди потерпілої особи. Це уможливлює висунення для фахового обговорення доктринального підходу, який полягає у відмові від прямого (текстуального) відображення у КК концепту «вік сексуальної згоди». Йдеться про те, що роль криміноутворювальної ознаки і в цьому разі відігравало не недосягнення потерпілою особою певного віку, визначеного у законодавчому порядку, а відсутність добровільної згоди потерпілої особи, як це і притаманно сексуальному насильству у сенсі Стамбульської конвенції. Показано, що це дозволило б, крім іншого, врахувати традиційну для вітчизняної судової практики і засновану на використанні поняття психічної безпорадності юридичну оцінку статевого акту з малолітньою особою та іншого сексуального проникнення в тіло такого потерпілого.
КОНВЕНЦІЙНИЙ КОНЦЕПТ «ВІК СЕКСУАЛЬНОЇ ЗГОДИ» У КРИМІНАЛЬНОМУ КОДЕКСІ УКРАЇНИ: СУЧАСНИЙ СТАН І ПЕРСПЕКТИВИ
Keywords: Istanbul Convention; Lanzarote Convention; age; voluntary agreement; sexual violence; helpless state; minor; child.; Стамбульська конвенція; Лансаротська конвенція; вік; добровільна згода; сексуальне насильство; безпорадний стан; малолітня особа; дитина.